IFN-β-inducing, unusual viral RNA species produced by paramyxovirus infection accumulated into distinct cytoplasmic structures in an RNA-type-dependent manner - Asuka eYoshida; Ryoko eKawabata; Tomoyuki eHonda; Keizo eTomonaga; Takemasa eSakaguchi; Takashi eIrie (Frontiers in Microbiology, 2015)
The interferon (IFN) system is one of the most important defensive responses of mammals against viruses, and is rapidly evoked when the pathogen-associated molecular patterns (PAMPs) of viruses are sensed. Non-self, virus-derived RNA species have been identified as the PAMPs of RNA viruses. In the present study, we compared different types of IFN-β-inducing and -non-inducing viruses in the context of Sendai virus (SeV) infection. We found that some types of unusual viral RNA species were produced by infections with IFN-β-inducing viruses and accumulated into distinct cytoplasmic structures in an RNA-type-dependent manner. One of these structures was similar to the so-called antiviral stress granules (avSGs) formed by an infection with IFN-inducing viruses whose C proteins were knocked-out or mutated. Non-encapsidated, unusual viral RNA harboring the 5’-terminal region of the viral genome as well as RIG-I and typical SG markers accumulated in these granules. Another was a non-SG-like inclusion formed by an infection with the Cantell strain; a copyback-type DI genome, but not an authentic viral genome, specifically accumulated in the inclusion, whereas RIG-I and SG markers did not. The induction of IFN-β was closely associated with the production of these unusual RNAs as well as the formation of the cytoplasmic structures.